Two new Dolichothele Mello-Leitão, 1923 species from Brazil and Bolivia (Araneae, Theraphosidae) - Revollo, Irene Soliz [UNESP]; da Silva Júnior, Pedro Ismael; Bertani, Rogério (Pensoft Publishers, 2017)
Two new species of Dolichothele Mello-Leitão, 1923 are described from Brazil and Bolivia, D. mottai sp. n. from Distrito Federal and the state of Goiás, Brazil, and D. camargorum sp. n. from the state of Rondônia, Brazil, and the La Paz region, Bolivia. Males of the two new species resemble Dolichothele bolivianum (Vol, 2001) in having a small subapical keel on the distal embolus and females in particular by the short spermatheca. Dolichothele bolivianum is redescribed, and its geographical distribution is herein restricted to Bolivia and the state of Mato Grosso in Brazil.
Keywords: Bolivia; Cerrado; Ischnocolinae; Tarantula; Taxonomy